Pengaruh Pengetahuan Keuangan terhadap Kesejahteraan Keuangan dengan Perilaku Keuangan sebagai Variabel Mediasi (Studi Kasus pada Mahasiswa S1 Manajemen Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya) - Siti Nur Laily Setiawati; Eko Wahjudi (Mataram University, 2026)
Student financial well-being is a crucial aspect supporting quality of life and future financial readiness. This study aims to analyze the influence of financial knowledge on studnt financial well-being, with financial behavior serving as a mediating variable. A quantitative research design with an explanatory approach was employed, utilizing proportionate stratified random sampling to select a sample of 128 students. The independent variable is financial knowledge, the mediating variable is financial behavior, and the dependent variable is student financial well-being. Data were collected via questionnaires developed based on indicators for each variable. Hypothesis testing was conducted using multiple linear regression analysis with SPSS version 25 software. The results indicate that financial knowledge does not have a significant effect on financial behavior or student financial well-being; conversely, financial behavior has a positive and significant effect on student financial well-being.